EXHUMATION: SOLVING MYSTERIES IN THE ABSENCE OF INITIAL POSTMORTEM - Jadoon, Omair Khan; Shazia, Salma; Haroon , Maimoona; Haroon, Zainab; Khan, Aftab Alam (Journal of Ayub Medical College Abbottabad, 2024)
Background: Stories of lives lived, unsolved mysteries, and undiscovered history are all hidden beneath the surface of the ground. Exhuming human remains is a voyage into the core of human existence, where the buried whisper their truths to the present. It is more than just a scientific procedure. This study was conducted to assess the reason of exhumation in cases where the initial postmortem was not performed. Methods: This retrospective study was conducted from August 2021 to August 2024. A total of 27 cases were studied at Ayub Teaching Hospital and Benazir Bhutto Shaheed Hospital, Abbottabad, under the supervision of the Forensic Medicine Department, Ayub Medical College. Data were collected and analyzed using Microsoft Excel. The findings were tabulated as frequencies and percentages. Result: Among 27 autopsy cases, the majority involved individuals aged 21–30 years. Most of the autopsies were of male. Determining the cause of death was the primary reason (47%), while the absence of an initial postmortem accounted for 19% of cases, highlighting procedural gaps. Three out of nine cases were confirmed as a natural death, while the remaining six involved unnatural causes. Conclusion: Exhumation serves as a vital tool in forensic investigations, particularly in cases where initial postmortems were not conducted.